1252 A Systematic Review of International Colorectal Multidisciplinary Team Meetings: The Development of Best Practice Through Inter-Regional Learning. (12th October 2021) - Fadel, M; Hamrang-Yousefi, S; Mills, S; Warren, O; Tekkis, P; Kontovounisios, C
Abstract: Aim: Colorectal multi-disciplinary teams (CR MDTs) were introduced to enhance the cancer care pathway and allow for early investigation and treatment of colorectal cancer. However, there are no gold standards set for this process. The aim of this study is to establish recommendations on the principles, organisation, structure and output of CR MDTs internationally. Method: The available literature on the role of CR MDTs from January 1999 and March 2020 in the United Kingdom (UK), United States of America (USA) and continental Europe was evaluated. Historical background, structure, core members, education, frequency, patient selection criteria, quality assurance, output and outcomes were extracted from data from the UK, USA, and continental Europe. Results: Fifty studies were identified that specifically met the inclusion criteria. CR MDTs should occur at least once a month with established key members. Generally, all colorectal cancer patients should be discussed and there should be a focus on education. There are noted differences in the lead member of the CR MDT, the use of information technology and storage of MDT information in databases and quality assurance internationally. Conclusions: The most common issues facing MDTs internationally include a lack of staffing and resources as well as limited information on the patient's fitness and preference for surgery. These factors are important and urgent improvements are required in these areas in CR MDTs. Quality assurance should be a mandatory component of every CR MDT.